2022
DOI: 10.1139/cjfas-2021-0302
|View full text |Cite
|
Sign up to set email alerts
|

Atlantic salmon survival at sea: temporal changes that lack regional synchrony

Abstract: Spatial and temporal synchrony in abundance or survival trends can be indicative of whether populations are affected by common environmental drivers. In Atlantic salmon (Salmo salar L.), return rates to natal rivers have generally been assumed to be affected primarily by shared oceanic conditions, leading to spatially synchronous trends in mortality. Here, we investigated the existence of parallel trends in salmon sea survival, using data on migrating smolts and returning adults from seven Canadian populations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 30 publications
1
7
0
Order By: Relevance
“…However, examination of the available empirical evidence failed to pinpoint the expected similarities in growth trajectories between European and North American populations (Barajas et al, 2021; Hogan & Friedland, 2010). This result is consistent with Tirronen et al (2022) who suggested a non‐stationarity and recent divergence in the ecological response of European and North American salmon populations. One exciting research avenue would be to extend our analysis to a larger set of populations across the North Atlantic basin to embrace more contrasting environments and a wider range of life histories.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…However, examination of the available empirical evidence failed to pinpoint the expected similarities in growth trajectories between European and North American populations (Barajas et al, 2021; Hogan & Friedland, 2010). This result is consistent with Tirronen et al (2022) who suggested a non‐stationarity and recent divergence in the ecological response of European and North American salmon populations. One exciting research avenue would be to extend our analysis to a larger set of populations across the North Atlantic basin to embrace more contrasting environments and a wider range of life histories.…”
Section: Discussionsupporting
confidence: 93%
“…Despite the growing evidence for pan‐population common signals in growth patterns, they are also subject to a large variability due to population‐specific signals. Indeed, location‐specific factors, such as local adaptation (Hutchings, 2011), carry‐over effects of local conditions in the freshwater phase (Gregory et al, 2017; Metcalfe & Thorpe, 1990), differences in migration timing (Jonsson et al, 2017) and migration routes, parasites or predation during the marine phase (Friedland et al, 2009; Tirronen et al, 2022; Vollset et al, 2022), are all likely to create variable responses between populations.…”
Section: Introductionmentioning
confidence: 99%
“…Improved understanding of salmonid metapopulation dynamics would require definitive, quantitative measures for a species in its spawning and early‐rearing habitat as well as in its habitat for subsequent growth and maturation elsewhere, as occurred for investigations of the YCT metapopulation of Yellowstone Lake. But attaining those measures for the entire metapopulation is challenging, particularly for spatially broad freshwater metapopulations and anadromous fishes, as recently shown by Tirronen et al (2022) for Atlantic salmon.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the substantial geographic variation in life‐history traits throughout their life cycle, previous studies have documented some level of spatial synchrony in Atlantic salmon population trends and demographic processes across broad geographic areas. This includes common long‐term trends in the abundance of adults (Friedland et al., 2014 ; Mills et al., 2013 ) and juveniles (Bouchard et al., 2022 ), productivity (Mills et al., 2013 ), survival during the early marine stage (i.e., post‐smolt stage) (Olmos et al., 2019 , 2020 , but see Pardo et al., 2021 ; Tirronen et al., 2022 ), the proportion of first‐time spawner age classes (Olmos et al., 2019 ) and repeat spawners compared to first‐time spawners (Bordeleau et al., 2019 ). Many of these synchronous processes have been linked to broad‐scale changes in the marine environment.…”
Section: Introductionmentioning
confidence: 99%